Billboard-Based Public Relations Communication Strategy to Support Public Information Disclosure in Serang City - Putri Handayani (JURNAL ILMIAH ILMU ADMINISTRASI, 2025)
Public information disclosure is an obligation of the regional government as mandated by Law Number 14 of 2008. However, in Serang City, the delivery of public information still faces various obstacles, such as limited access to information, low public understanding of public policies, and the suboptimal use of easily accessible communication media. Billboards as a public visual communication medium have not been fully maximized by the local government's Public Relations as a strategic means to convey transparent, accurate, and easily understood information. This study aims to analyze billboard-based Public Relations communication strategies in supporting public information disclosure in Serang City and identify their effectiveness in increasing public understanding and trust. This study uses a qualitative method with a descriptive approach. Data collection techniques include observation of government billboards, interviews with Public Relations officials and the community, and documentation of policies and public communication materials. The results show that billboards have a strategic role as a Public Relations communication medium in supporting public information disclosure in Serang City. Simple message strategies, attractive visuals, and appropriate placement have been proven to increase information accessibility and strengthen transparency and a positive image of the local government.